Optimalisasi Penerapan Fungsi Pengendalian (Controling) dalam Meningkatkan Kemampuan Evaluasi Kegiatan Siswa SMK Makarya 1 - Ade Amelia; Karina Zahwa Safina; Ega Gastiadirriza; Ahmad Nurhadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Student activities in Vocational High Schools (SMKs) require the proper implementation of management functions, particularly the controlling function, to ensure that every activity is carried out effectively and achieves optimal outcomes. However, based on the preliminary observations conducted at SMK Makarya 1, the evaluation process of student activities had not been implemented systematically, resulting in evaluation findings that were not optimally utilized as a basis for improving subsequent activities. This community service program aimed to enhance students' understanding of the controlling function and improve their ability to evaluate school activities effectively. The implementation methods consisted of preparation, interactive lectures, discussions and question-and-answer sessions, student mentoring, motivational activities, and program evaluation through observation and documentation. The results indicated an improvement in students' understanding of the importance of the controlling function in school and organizational activities. Students were able to recognize that evaluation is an essential component of the management process to identify obstacles, assess the level of activity achievement, and formulate recommendations for future improvements. Therefore, this community service program made a positive contribution to enhancing students' ability to evaluate school activities while fostering a more systematic, objective, and continuous improvement-oriented controlling culture at SMK Makarya 1.